Síntese de agentes hemostáticos coagulantes com base em materiais zeolíticos - Araújo, Marcelo Valdemir de [UNESP] (2013)
The main goals of this research work were the synthesis and characterization of different types of zeolites and evaluation of their use as hemostatic agents. Initially, three differents zeolites were synthesized: faujasite (FAU), gismondine (GIS) and mordenite (MOR). The three zeolites were first prepared in their sodium form and thereafter they were submitted to an ion exchange process in order to the replace extra-framework Ca2+. After characterization these materials, were assessed in their potential as hemostatic agents, both the sodium as weel as the calcium forms, in vitro tests using thromboelastography. In order obtain comparative data was used in testing agent hemostatic already know, the Kaolin. The resultds showed that all six zeolites materials have successfully as a agent hemostatic reducing the coagulation time and increasing the rate of clot thrombin generation. Altrought, zeolite GIS/Ca2+ to be more efficient in general parameters such as rate of generation (K), thrombin generation rates (α) and elastic property of fibrin (AM), while the results showed MOR/Ca2+ less efficient in the general parameters of coagulation, showing that its structure is difficult acess to Ca2+ in the ion exchange process